Successful use of Single dose of Methotrexate for the treatment of Unruptured Ectopic Pregnancy at Tribhuvan University Teaching Hospital, Kathmandu, Nepal - Rawal, Suniti (Nepal Journal of Obstetrics and Gynaecology, 2013)
Ectopic pregnancy continues to be one of the most common gynecologic emergencies. The incidence of ectopic pregnancies which are diagnosed much earlier with the help of advanced tools is in the increasing trend, probably due to extensive use of assisted reproductive technologies and increased pelvic infections. A total of 36 ectopic pregnancies were managed from April 2007- March 2008 among which 33 were ruptured ectopics with haemoperitoneum, treated surgically by emergency laparotomy and salpingectomy. Three unruptured cases were treated with single dose of intramuscular methotrexate followed by serum ß hCG measurement. Transvaginal sonography reassured that medical management of unruptured ectopic pregnancies with systemic single dose of methotrexate was successful with few side effects and a cost effective alternative to traditional surgical management for unruptured ectopic pregnancies. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 45-49 DOI: http://dx.doi.org/10.3126/njog.v7i1.8836